2019
DOI: 10.1038/s41598-018-37571-x
|View full text |Cite
|
Sign up to set email alerts
|

The NOP-1 peptide derived from the central regulator of ethylene signaling EIN2 delays floral senescence in cut flowers

Abstract: The plant hormone ethylene was identified as important triggering factor and primary regulator of flower senescence in many species. Consequently, application of chemical inhibitors of ethylene biosynthesis and action is used to extend the longevity of ethylene-sensitive flowers. Here, we show that the peptide NOP-1, a biological derived from the nuclear localization signal of ethylene regulator EIN2 tightly binds to the ethylene receptor of carnation plants - a model to study flower senescence. When applied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This peptide corresponds to the NLS in EIN2-C and disrupts the interaction between EIN2 and ETR1 in Arabidopsis as well as interactions between SlETR1 and SlEIN2 in tomato (121,228). NOP-1 binds to various ethylene receptors including ETR1 from Arabidopsis, NR and SlETR4 from tomato, and DcETR1 from carnation (229)(230)(231). Importantly, NOP-1 leads to reduced ethylene sensitivity in various plants and has been shown to delay tomato fruit ripening and carnation flower senescence (121,230).…”
Section: Regulating Ethylene Signal Transduction For Agricultural Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This peptide corresponds to the NLS in EIN2-C and disrupts the interaction between EIN2 and ETR1 in Arabidopsis as well as interactions between SlETR1 and SlEIN2 in tomato (121,228). NOP-1 binds to various ethylene receptors including ETR1 from Arabidopsis, NR and SlETR4 from tomato, and DcETR1 from carnation (229)(230)(231). Importantly, NOP-1 leads to reduced ethylene sensitivity in various plants and has been shown to delay tomato fruit ripening and carnation flower senescence (121,230).…”
Section: Regulating Ethylene Signal Transduction For Agricultural Andmentioning
confidence: 99%
“…Also important is that it can achieve these effects by surface application to the plants. Since the NLS sequence in EIN2s is conserved across many flowering ornamental species (229), it is very likely that NOP-1 and derivatives will be effective at blocking ethylene responses in most, if not all, plants used in agriculture and horticulture.…”
Section: Regulating Ethylene Signal Transduction For Agricultural Andmentioning
confidence: 99%
“…For instance, in our lab, interaction of the type-I receptor ETR1 with EIN2 479-1294 was demonstrated by in vivo FRET-studies and quantified by in vitro tryptophan fluorescence quench analysis (Bisson et al., 2009). Moreover, recent studies in our lab highlighted that the conserved nuclear localization signal (NLS) sequence of EIN2 significantly contributes to the EIN2-receptor interaction and in the form of a synthetic octapeptide (NOP1) delays fruit ripening and flower senescence (Bisson et al., 2016; Kessenbrock et al., 2017; Milić et al., 2018; Hoppen et al., 2019). In contrast, related information on ethylene receptor subfamily-II is still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel method has been employed for retarding flower senescence and delaying post-harvest fruit ripening via application of synthetic octapeptide LKRYKRRL-NH2 (NOP-1) in carnation cut flowers [5], roses [6], tomatoes [7] and cut broccoli florets [8]. Studies on ethylene signaling pathways and mechanisms in model plant Arabidopsis thaliana has demonstrated that the endoplasmic reticulum (ER) integral membrane protein ETHYLENE IN-SENSITIVE 2 (EIN2) implements a positive regulatory role on ethylene signaling cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on ethylene signaling pathways and mechanisms in model plant Arabidopsis thaliana has demonstrated that the endoplasmic reticulum (ER) integral membrane protein ETHYLENE IN-SENSITIVE 2 (EIN2) implements a positive regulatory role on ethylene signaling cascades. The EIN2 protein undergoes phosphorylationdependent proteolytic processing and translocation of a highly conserved NLS (nuclear localization signal) at the EIN2 C-terminal into the nucleus to induce expression of ethylene responsive genes [6]. The NOP-1 peptide mimics the NLS motif of EIN2 and competitively binds to the GAF (cGMP-specific phosphodiesterase, adenylyl cyclases, and FhlA) domain of Ethylene Receptor -1 (ETR-1).…”
Section: Introductionmentioning
confidence: 99%